Relações de gênero na escola: desconstruindo estereótipos na Educação Infantil - LIMA, Stefany Machado de (2025)
The research titled Gender Relations in School: Deconstructing Stereotypes in Early Childhood Education analyzes the influence of gender stereotypes on children's choices and behaviors, as well as their impact on identity formation. The study seeks to understand how schools and their agents contribute to either the perpetuation or the deconstruction of sexist stereotypes, proposing pedagogical interventions that promote gender equity from early childhood education onward. The research adopts a qualitative approach, with a methodological pathway that included a literature review, document analysis, and field data collection. The document analysis was based on official materials such as the Curricular Document of the Maranhão Territory and the Curricular Proposal for Early Childhood Education of São Luís. Additionally, semi- structured interviews with early childhood education teachers and observations of school routines were conducted to understand pedagogical practices and educators perceptions of gender relations. Grounded in authors such as Beauvoir, Foucault, Louro, and Scott, the dissertation discusses concepts of gender, stereotypes, and historical inequalities, analyzing how these issues are reflected in the school environment. The investigation revealed that gender stereotypes are often normalized in interactions between children and adults, reinforcing behavior patterns associated with masculinity and femininity. It also identified significant challenges faced by teachers in addressing the topic, including a lack of specific training, cultural resistance, and insufficient teaching materials. As a result, a Guide for Didactic and Pedagogical Guidelines on Gender Relations was developed collaboratively with teachers and children. The guide provides practical strategies for deconstructing stereotypes and promoting inclusive and equitable education. The research concludes that raising awareness and providing continuous training for teachers, combined with the transversal incorporation of gender discussions into curricula, are essential to transforming schools into spaces of equality and respect.